A geochemical assessment of old slimes tailings from two South African kimberlite diamond mines : implications for mineral-carbonation resource estimation - Zakhele, Nkosi (University of Pretoria, 2025)
Dissertation (MSc (Geology))--University of Pretoria, 2025.